Предмет: Алгебра,
автор: jacket321
представьте выражение в виде произведения a) x(a-c)-ay+cy б) a(x-y)+by-bx в) c(m+n)-dm-dn
Ответы
Автор ответа:
0
a) x(a-c)-ay+cy=x(a-c)-(ay+cy)=x(a-c)-(y(a+c))=x(a-c)-y(a-c)=(a-c)(x-y)
б) a(x-y)+by-bx=a(x-y)+b(y-x)=a(x-y)-b(x-y)=(x-y)(a-b)
в) c(m+n)-dm-dn=c(m+n)-(dm-dn)=c(m+n)-(d(m-n))=c(m+n)-d(m+n)=(m+n)(c-d)
б) a(x-y)+by-bx=a(x-y)+b(y-x)=a(x-y)-b(x-y)=(x-y)(a-b)
в) c(m+n)-dm-dn=c(m+n)-(dm-dn)=c(m+n)-(d(m-n))=c(m+n)-d(m+n)=(m+n)(c-d)
Похожие вопросы
Предмет: Алгебра,
автор: zenitsuhz
Предмет: Алгебра,
автор: viktoriaprudeckaa038
Предмет: Геометрия,
автор: t9a3jtjv7f
Предмет: Математика,
автор: ramil44444444
Предмет: Математика,
автор: Antonacci796